Recording gear-type pump acoustic signals for assessing the hydraulic oil impurity level in a hydraulic excavator transmission - Ivanov Sergey (EDP Sciences, 2021)
Mechanization and development of mining machines increase the importance of maintenance quality of working bodies and the machines themselves. This requires implementing improvements in technical maintenance processes. Improving technical maintenance implies the implementation of condition monitored maintenance that also allows real-time monitoring of the technical status. As hydraulic oil pollution is one of the major causes of breakdowns, it is recommended to implement oil pollution monitoring methods that will allow estimating the real-time oil pollution level. Today, sampling is the most widespread method of pollution level control. This method is time-consuming and that is why there are many attempts to devise new methods of monitoring the real-time oil pollution level. One of such methods includes recording of the acoustic-emission signal. In this work, we suggested that increase in transmission oil pollution level leads to increase in acoustic-emission signal in 20-300 kHz range. This increase in the acoustic level will indicate the pollution of oil with solid particles and alert the maintenance crew of the necessity of replacing the oil. This method allows real-time monitoring the hydraulic oil condition not associated with high labor, time, or economic costs.